A Career Stage Analysis of the U.S. Federal Employees' Job Satisfaction and Turnover Intention: A Comprehensive Overview. (December 2020) - Lee, Hyung-Woo
This study examines how the determinants of job satisfaction and turnover intention are different across employee's career stages, using a large-scale data set from U.S. federal agencies. A comprehensive examination of career stage differences provides a sophisticated understanding of the multifaceted nature of job satisfaction and turnover intention factors. The trajectory of career stage differences is linear, and the impact of career stages is rather minimal when it comes to the determinants of job satisfaction, whereas the differences in terms of turnover intention were more drastic and salient. Also, the patterns of career stage effect were more complicated than proposed in the existing studies. The implications of these findings are explored for future research and practitioners.